2010
DOI: 10.1128/jvi.01928-09
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Porcine Endogenous Retrovirus Release by Porcine and Human Tetherins

Abstract: The risk of transmission of porcine endogenous retrovirus (PERV) is one of the major safety issues in xenotransplantation. Human tetherin, recently described as an antiviral protein able to inhibit the release of enveloped viruses, and its porcine homologue were shown to inhibit PERV release from producer cells, establishing themselves as candidate molecules to suppress PERV production in porcine xenografts by animal engineering.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 26 publications
1
33
0
1
Order By: Relevance
“…However, overexpression of either human or porcine tetherin in pig cells significantly reduced PERV production (205).…”
Section: Pervsmentioning
confidence: 99%
“…However, overexpression of either human or porcine tetherin in pig cells significantly reduced PERV production (205).…”
Section: Pervsmentioning
confidence: 99%
“…In fact, inhibition of virus release by BST-2 is not HIV-1 specific but affects other lentiviruses, such as HIV-2 and simian immunodeficiency virus (SIV), as well as a wide variety of enveloped viruses, including Ebola virus, Lassa virus, Marburg virus, Kaposi sarcoma-associated herpesvirus (KSHV), porcine endogenous retrovirus (PERV), and endogenous betaretrovirus of sheep (18)(19)(20)(21)(22)(23). Three different lentiviral proteins, HIV-1 Vpu, HIV-2 Env, and SIV Nef, have been found to antagonize the activity of their natural host, BST-2, thus allowing for efficient particle release from BST-2-expressing cells.…”
mentioning
confidence: 99%
“…Later, it was found that human tetherin has very broad antiviral activities, which also target many other enveloped viruses, including retroviruses, filoviruses, arenaviruses, paramyxoviruses, herpesviruses, and rhabdoviruses (2)(3)(4)(5)(6)(7)(8)(9). Human tetherin orthologs have been isolated from several other species, including monkey, cat, pig, mouse, cattle, and sheep, which all show similar antiviral activities (10)(11)(12)(13)(14)(15)(16)(17).…”
mentioning
confidence: 99%